Agent-based simulation to evaluate and categorize industrial symbiosis indicators. (10th June 2018) - Mantese, Gabriel Couto; Amaral, Daniel Capaldo
Abstract: There is a research effort towards the understanding of industrial symbiosis and part of it is directed to the development of performance indicators. The result is a variety of indicators, which hinders the evaluation, comparison, and decision by researchers and practitioners. This paper presents a comparative evaluation of the industrial symbiosis indicators available in the literature. The indicators were simulated through an agent-based model in two distinct scenarios, in a stable environment and in one with significant changes. The behaviors of the indicators were compared and the results allowed the classification of the indicators into three groups: (i) those related to the amount of by-products reused; (ii) those that behave according to the percentage of by-products reused; (iii) those influenced by the number of links. Considering the differences in performance and complexity, amount of information for calculation, it is concluded that the best alternative is to combine indicators from different groups. The indicators Connectance & Eco-Connectance (simplicity), Eco-Efficiency (overall park impact), and Industrial Symbiosis Indicator (flexibility) stood out. The simulation proved to be a platform that can be used for the study and development of these indicators. Highlights: Agent-based model platform for evaluation of industrial symbiosis indicators. Simulation of 9 industrial symbiosis indicators through extreme conditions scenarios. Identification of indicators categories according to their behavior in simulations. Industrial Symbiosis Indicator and Eco-Efficiency reacted proper in extreme condition. Combined use of Industrial Symbiosis Indicator, Eco-Efficiency and Eco-Connectance.